Students’ Interest in Entrepreneurship After Following Entrepreneurship Practice of “Indonesian Traditional Snack Creation” - Nova Pratiwi; Januardi (Jurnal Ekonomi, 2020)
This research attempted to describe students' interest in entrepreneurship after following the entrepreneurship practice of "Indonesian Traditional Snack Creation". This was a qualitative descriptive research whose informants were elementary school teacher education study program students of PGRI University of Palembang, who took entrepreneurship courses and amounted to 36 students. Data collection was done using questionnaires and interviews. The research results showed that although business activities were carried out independently in their houses due to the Covid-19 pandemic, that did not reduce students' enthusiasm, optimism, and creativity. This was evident from the various traditional snack creations presented in their sales reports. Students’ interest in entrepreneurship tends to be high and medium, with more than 50% of students who participated in entrepreneurship practice planned to start their own entrepreneurship in the near future to the next 2 years. The entrepreneurship practice of “Indonesian Traditional Snack Creation” could provide the students with the ability to create their own job opportunities for others and become solution to unemployment.